2019
DOI: 10.1122/1.5108919
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between morphology, rheological behavior, and electrical behavior of conductive cocontinuous LLDPE/EVA blends containing commercial graphene nanoplatelets

Abstract: In this work, co-continuous blends of linear low density polyethylene (LLDPE)/ Ethyl vinyl acetate (EVA) containing graphene (GN) have been studied. Although mass-produced GN grade prepared by mechanochemical exfoliation of graphite and a facile melt compounding technique were adopted, it was possible to lower the electrical percolation threshold significantly by controlling the localization of GN nanoplatelets in the blend and by applying an appropriate thermal annealing procedure. The electrical and rheologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 70 publications
4
20
0
Order By: Relevance
“…The whole treatment took 1 h 10 min ( Figure 1 ). The starting temperature of the treatment (160 °C) was chosen to prevent the so-called annealing effect [ 11 , 14 , 29 , 30 , 31 , 49 ] which could involve the coarsening of blend morphology. The temperature of 135 °C at the end of the treatment corresponds to the highest onset temperature of crystallization, evaluated by the DSC analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole treatment took 1 h 10 min ( Figure 1 ). The starting temperature of the treatment (160 °C) was chosen to prevent the so-called annealing effect [ 11 , 14 , 29 , 30 , 31 , 49 ] which could involve the coarsening of blend morphology. The temperature of 135 °C at the end of the treatment corresponds to the highest onset temperature of crystallization, evaluated by the DSC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Conductive nanocomposites are obtained by dispersing electrically conductive nanoparticles (particles with at least one of their dimensions ranging from 1 to 100 nm) within a matrix. The most used nanoparticles to obtain electrically conductive polymers are carbon black (CB) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], carbon nanotubes (CNTs) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 24 , 25 , 26 , 27 , 28 ], and graphene [ 12 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Due to the advantages conductive thermoplastic composites present, significant research has been conducted towards achieving certain desired properties at low filler concentrations, primarily by reducing the percolation threshold (PT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, graphene, which consists of sp 2 -hybridized networks of carbon atoms in two dimensional hexagonal structures with one atom thickness, started gaining interest as a novel multifunctional additive that may effectively replace conventional light stabilizers, which are mostly specific in their action [13,14]. In addition to its excellent photostabilizing properties, which will be discussed in details in this article, graphene features promising electrical, mechanical, thermal, and chemical properties [15][16][17][18] attracting worldwide attention in the academic and industrial fields as a promising candidate for various applications [19][20][21][22]. Furthermore, the recent progress in large-volume and cost-effective manufacturing of few-layer graphene has made it an economically viable choice for the plastics industry.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a significant amount of research has been conducted on the area of matrix modification by GNP, with remarkable outcomes. For instance, GNP-filled polymers showed improved mechanical [6], electrical [7], gas barrier [8] and heat conduction [9] properties. Moreover, recent studies on the gene toxicity of GNP have concluded that graphene is much safer than carbon black for large-scale use [10].…”
Section: Introductionmentioning
confidence: 99%